Effect of Bio-Electrochemical Treatment of Hydroponic Effluent on the Nutrient Content - Kamil Łukasz Bryszewski; Joanna Rodziewicz; Wojciech Janczukowicz (Applied Sciences, 2022)
This study examined the effect of bio-electrochemical treatment processes on nitrogen and phosphorus removal, but it also evaluated the impact of the treatment processes on the concentration of other nutrients present in hydroponic effluent. A bio-electrochemical reactor (BER) was used in the experiment to treat effluent from the hydroponic cultivation of tomatoes. It was stated that the nitrogen removal efficiency decreased with increasing current density. The study showed that an electric current density of 0.63 A/m2 ensured the lowest effluent nitrate concentration. The nitrogen removal efficiency ranged from 41.6%-R1 (density of 0.63 A/m2) to 8.9%-R4 (density of 5 A/m2). Electric current density higher than 1.25 A/m2 resulted in lower total nitrogen removal efficiency. The total phosphorus removal efficiency increased with increasing electric current density. The phosphorus removal efficiency was the lowest—95.1%—in the R1 reactor, whereas it was the highest in R4—99.1%. The concentration of the other elements in the effluent was determined. The content of molybdenum, boron, sulphates, and potassium did not meet the acceptable norms for discharging hydroponic effluent into the environment. The study showed that bio-electrochemical processes taking place in BER caused secondary contamination of hydroponic wastewater with molybdenum ions.